2014
DOI: 10.5897/ajb2014.13747
|View full text |Cite
|
Sign up to set email alerts
|

Assessing relationship between phenolic compounds and resistance to Phytophthora megakarya using two cocoa (Theobroma cacao) families

Abstract: Black pod disease is an important fungal infection in cocoa (Theobroma cacao L.) which causes high production losses. In Cameroon, these losses reached 80% of cocoa production depending on ecological zones. In order to contribute to the efficiency of selection methods used in resistance or tolerance to black pod disease with the aim of improving on cocoa farming, the content of phenolic compounds was analyzed on the genotypes of two hybrid families (F79:♀T 79/467 x♂SNK 13 and F13:♀SNK 13 x♂T 79/467) of cocoa w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
1
8
0
1
Order By: Relevance
“…This increase was due to the activation of phenylalanine ammonia lyases (PAL), the enzymes most involved in phenolic metabolism, by the elicitors produced by P. megakarya. Our results are in agreement with those of Simo et al (2014) indicated that the increase in phenolic content under infectious conditions was greater in tolerant individuals [14]. These results are also in agreement with those obtained by Effa et al (2017) who found that parental or hybrid tolerant genotypes accumulated elevated total phenolic compounds relative to susceptible hybrid genotypes after infection of pods with P. megakarya mycelium [27].…”
Section: Evaluation Of Phenolic Compound Content After Leaf Infectionsupporting
confidence: 93%
See 2 more Smart Citations
“…This increase was due to the activation of phenylalanine ammonia lyases (PAL), the enzymes most involved in phenolic metabolism, by the elicitors produced by P. megakarya. Our results are in agreement with those of Simo et al (2014) indicated that the increase in phenolic content under infectious conditions was greater in tolerant individuals [14]. These results are also in agreement with those obtained by Effa et al (2017) who found that parental or hybrid tolerant genotypes accumulated elevated total phenolic compounds relative to susceptible hybrid genotypes after infection of pods with P. megakarya mycelium [27].…”
Section: Evaluation Of Phenolic Compound Content After Leaf Infectionsupporting
confidence: 93%
“…The extraction of phenolic compounds for quantitative analysis was done according to the method described by Simo et al (2014) [14]. Twenty mg of fresh leaf cut past the necrotic part were crushed in 5ml of methanol (80%) by adding a pinch of sterile fine sand and the resulting maceration was centrifuged at 6000 g for 20 min.…”
Section: Extraction and Content Assessment Of Phenolic Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study assessing relationship between phenolic compounds and resistance to P. megakarya using two cocoa families, some authors [32]found that productive and tolerant genotypes displayed high phenols content meanwhile less tolerant and productive ones had a weak content. The role of phenolic compounds in plant defense is well documented [33]. These metabolites accumulate at different levels in infected tissues in response to pathogen attack.…”
Section: Discussionmentioning
confidence: 99%
“…Beberapa karakter komponen buah kakao, yang meliputi ukuran buah (pod), biji, kulit buah, dan pulpa, berhubungan langsung dengan produktivitas tanaman serta ketahanan terhadap hama penggerek buah (PBK) (Susilo, Mangoendidjojo, Witjaksono, Sulistyowati, & Mawardi, 2009;Wijaya, Prawoto, & Ihromi, 2009;Asrul, Agus, Daryati, & Mollah, 2012;Limbongan, 2012;Pertiwi, Asrul, & Baja, 2013;Susilo, Mawardi, Witjaksono, & Mangoendidjojo, 2015) dan penyakit busuk buah Ondobo et al, 2014;Simo et al, 2014) .…”
Section: Pendahuluanunclassified